2010
DOI: 10.1002/chem.200903258
|View full text |Cite
|
Sign up to set email alerts
|

PAMAM Dendrimers for siRNA Delivery: Computational and Experimental Insights

Abstract: Short double-stranded RNAs, which are known as short interfering RNA (siRNA), can be used to specifically down-regulate the expression of the targeted gene in a process known as RNA interference (RNAi). However, the success of gene silencing applications based on the use of synthetic siRNA critically depends on efficient intracellular delivery. Polycationic branched macromolecules such as poly(amidoamine) (PAMAM) dendrimers show a strong binding affinity for RNA molecules and, hence, can provide an effective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 69 publications
2
71
0
Order By: Relevance
“…Recently, DOSY experiments were employed to determine the effect of palladium nanoparticles in the structure and diffusion properties of G4 and G6 PAMAM dendrimers, showing that these dendrimers do not form dendrimer metallic nanoparticles aggregates in solution [22,23]. In 2010, Pavan et al reported the diffusion coefficients of G4-G6 PAMAM dendrimers and their supramolecular complexes with siRNA, using a combined strategy of computational methods and DOSY experiments, showing that calculated structural parameters for PAMAM dendrimers at different pH were in excellent agreement with the actual NMR experiments [24]. Self-diffusion of lower generation G0-G3 PAMAM dendrimers has not been studied by experimental methods in aqueous solution.…”
Section: Introductionmentioning
confidence: 72%
“…Recently, DOSY experiments were employed to determine the effect of palladium nanoparticles in the structure and diffusion properties of G4 and G6 PAMAM dendrimers, showing that these dendrimers do not form dendrimer metallic nanoparticles aggregates in solution [22,23]. In 2010, Pavan et al reported the diffusion coefficients of G4-G6 PAMAM dendrimers and their supramolecular complexes with siRNA, using a combined strategy of computational methods and DOSY experiments, showing that calculated structural parameters for PAMAM dendrimers at different pH were in excellent agreement with the actual NMR experiments [24]. Self-diffusion of lower generation G0-G3 PAMAM dendrimers has not been studied by experimental methods in aqueous solution.…”
Section: Introductionmentioning
confidence: 72%
“…Atomic simulations of dendrimer-nucleic acid interactions have been conducted by Nandy et al and the study showed the formation of stable DNA and siRNA complexes with PAMAM dendrimers at a physiological pH based on electrostatic interaction. 40 The strong binding affinity of PAMAM dendrimers to the RNA has also been shown in computational and experimental designs by 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Pavan et al 41 The dose and time dependent changes on the nucleolus of the A549 cells upon PAMAM-G5 exposure are also evaluated in order to clarify mechanism of action of PAMAM-G5 dendrimers with RNA. The scatter plots of PCA of nucleolus of PAMAM-G5 exposed A549 cells and corresponding controls are provided in Supplementary Figure S9 and S10 for dose dependent and time dependent responses, respectively.…”
Section: Page 19 Of 30 Analystmentioning
confidence: 92%
“…Modifications to the dendrimer surface, such as attaching sugar molecules (cyclodextrins) [39] and hydrophobic dye molecules (Oregon green 488) [40], have been found to improve transfection efficiency; however, the underlying transfection mechanisms are still unclear. However, the molecular mechanisms underlying complexation between short doubled stranded RNA (siRNA) and PAMAM dendrimers have been described by Pavan et al [41] using molecular simulation, NMR and electrophoresis assays. Electrostatic complexation of anionic DNA with cationic dendrimers has also been shown to result in the formation of DNA-linked PAMAM nanoclusters as described by MD simulations by Madal et al [42].…”
Section: Gene Transfectionmentioning
confidence: 99%